Machine Learning Methods in Systems Proceedings of 13th Computer Science On-line Conference 2024, Vol. 4 - Silhavy, Radek; Silhavy, Petr (Lecture Notes in Networks and Systems, 2024)
XV, 520 p. 193 illus., 139 illus. in color.